Universal versus platelet reactivity assay-driven use of P2Y12 inhibitors in acute coronary syndrome patients - Coleman, Craig I.; Limone, Brendan L. (Thrombosis and Haemostasis, 2014)
Platelet reactivity assays (PRAs) can predict patients’ likely response to clopidogrel. As ticagrelor and prasugrel are typically considered first-line agents for acute coronary syndrome in Europe, we assessed the cost-effectiveness of universal compared to PRA-driven selection of these agents. A Markov model was used to calculate five-year costs (2013£/€), quality-adjusted life-years and incremental cost-effectiveness ratios (ICERs) for one-year of universal ticagrelor or prasugrel (given to all) compared to each agents’ corresponding PRA-driven strategy (ticagrelor/prasugrel in those with high platelet reactivity [HPR, >208 on the VerifyNow P2Y12 assay], others given generic clopidogrel). We assumed patients had their index event at 65–70 years of age and had a 42.7% incidence of HPR 24–48 hours post-revascularisation. The analysis was conducted from the perspective of six countries (France, Germany, Italy, Spain, the Netherlands and United Kingdom) and used a one-year cycle length. Event data for P2Y12 inhibitors were taken from multinational randomised trials and adjusted using country-specific epidemiologic data. Neither universal ticagrelor nor prasugrel were found to be cost-effective (all ICERs >40,250€ or £36,600/QALY) compared to their corresponding PRA-driven strategies in any of the countries evaluated. Results were sensitive to differences in P2Y12 Inhibitors costs and drug-specific relative risks of major adverse cardiac events. Monte Carlo simulation suggested universal ticagrelor or prasugrel were cost-effective in only 25–44% and 11–17% of 10,000 iterations compared to their respective PRA-driven strategies, when applying a willingness-to-pay threshold = €30,000 or £20,000/QALY. In conclusion, the universal use of newer P2Y12 inhibitors is not likely cost-effective compared to PRA-driven strategies.
Keywords: Platelet reactivity assay; acute coronary syndrome; antiplatelet agents; cost-effectiveness analysis; Markov model